2018
DOI: 10.1111/pde.13596
|View full text |Cite
|
Sign up to set email alerts
|

Topical rapamycin (sirolimus) for the treatment of uncomplicated tufted angiomas in two children and review of the literature

Abstract: The mTOR inhibitor rapamycin is used systemically for the treatment of vascular lesions. We report the first use of topical rapamycin for the successful treatment of two cases of tufted angioma. The evidence for the use of topical rapamycin in other dermatologic conditions is summarized to aid in clinical decision making on preparations and anticipated side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Three retrospective studies described the benefits of topical sirolimus in the treatment of tufted angiomas. 10,50,51 A decrease in lesion size was reported for all patients, but no clinical benefit was described for the infantile hemangioma.…”
Section: Vascular Tumorsmentioning
confidence: 93%
“…Three retrospective studies described the benefits of topical sirolimus in the treatment of tufted angiomas. 10,50,51 A decrease in lesion size was reported for all patients, but no clinical benefit was described for the infantile hemangioma.…”
Section: Vascular Tumorsmentioning
confidence: 93%
“…Several case reports and case series have reported success using topical sirolimus and tacrolimus ointment in superficial KHE/TA. The investigators have shown a good response of KHE/TA to twice daily topical application of these drugs [130,131]. Tacrolimus is an anti-T-cell immunosuppressive drug that is FDA-approved as a topical gel formulation (available in a concentration of 0.03 and 0.1%) for the treatment of cutaneous inflammatory/fibrotic diseases [132].…”
Section: Topical Treatmentsmentioning
confidence: 99%
“…Therefore, vincristine is now primarily preferred for refractory or recurrent cases. Topical sirolimus or tacrolimus have been shown in small studies to be beneficial for superficial cutaneous lesions but not for KHE with KMP 33,34 . Antiplatelet therapy such as aspirin or ticlopidine in combination with vincristine have also shown success 35–38 .…”
Section: Case 1: Khe With Kmpmentioning
confidence: 99%